Pemberdayaan Warga Desa Joho Melalui Demonstrasi Pembuatan Pestisida Nabati dan Sosialiasi Penggunaan Aplikasi Plantix untuk Deteksi Penyakit Tanaman - Ahmad Naufal Attaqi; Kharunia Prameswari; Putri Isna; Prasetyo Budi Utomo; Dita Avrelia; Savrina Dewi; Ryan Nashrullah; Yosi Yosi; Deyan Wulan; Muhammad Rizieq; Mayla Keyza; Anisa Nur Mareta; Raihanatu Qalbi (Abdi Jaya : Jurnal Pengabdian Indonesia, 2025)
A community service program implemented in Joho Village, Bawang District, Banjarnegara Regency, aims to strengthen farmers' awareness and practical skills in managing plant pests and diseases. Farmers in the region have long relied on synthetic pesticides that can damage the environment, and have limited capacity to identify plant health problems. To address these issues, the program introduced educational sessions and hands-on demonstrations, focusing on the creation of environmentally friendly botanical pesticides using tobacco, garlic, and galangal, as well as training on the Plantix mobile app for diagnosing plant diseases. Results showed that participants gained a better understanding of the benefits of botanical pesticides and were able to operate the Plantix app independently. Overall, this initiative offers a sustainable, environmentally friendly approach to pest and disease control while contributing to increased agricultural productivity.